Design, recruitment, and microbiological considerations in human challenge studies. Issue 7 (July 2015) - Darton, Thomas C; Blohmke, Christoph J; Moorthy, Vasee S; Altmann, Daniel M; Hayden, Frederick G; Clutterbuck, Elizabeth A; Levine, Myron M; Hill, Adrian V S; Pollard, Andrew J
Summary Since the 18th century a wealth of knowledge regarding infectious disease pathogenesis, prevention, and treatment has been accumulated from findings of infection challenges in human beings. Partly because of improvements to ethical and regulatory guidance, human challenge studies—involving the deliberate exposure of participants to infectious substances—have had a resurgence in popularity in the past few years, in particular for the assessment of vaccines. To provide an overview of the potential use of challenge models, we present historical reports and contemporary views from experts in this type of research. A range of challenge models and practical approaches to generate important data exist and are used to expedite vaccine and therapeutic development and to support public health modelling and interventions. Although human challenge studies provide a unique opportunity to address complex research questions, participant and investigator safety is paramount. To increase the collaborative effort and future success of this area of research, we recommend the development of consensus frameworks and sharing of best practices between investigators. Furthermore, standardisation of challenge procedures and regulatory guidance will help with the feasibility for using challenge models in clinical testing of new disease intervention strategies.